1998
DOI: 10.1136/vr.142.7.162
|View full text |Cite
|
Sign up to set email alerts
|

South American camelids in the United Kingdom: population statistics, mortality rates and causes of death

Abstract: A survey of the health of South American camelids in the United Kingdom was carried out between December 1992 and June 1993; 123 members of the British Camelid Owners and Breeders Association and 19 non-members were sent questionnaires and usable responses were received from 84 (59 per cent). In total 689 camelids were included, and in 1992, 66 per cent were Ilama, 21 per cent alpaca and 13 per cent guanaco. Their ages ranged from less than six months to over 10 years, with animals aged two to five years const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 0 publications
2
27
2
1
Order By: Relevance
“…Population, Haltung und Gesundheitsprobleme I. Hengrave Burri 1 , J. Martig 1 , H. Sager 2 , A. Liesegang 3 , M. Meylan 1 1 Wiederkäuerklinik und 2 Institut für Parasitologie der Universität Bern, 3 Institut für Tierernährung der Universität Zürich Einleitung Die Popularität der Neuweltkameliden (NWK) hat in den letzten Jahren ständig zugenommen. Ihre Population wächst stetig, nicht nur in den USA (Smith, 1998), wo das Interesse für diese Tiere schon seit Jahrzehnten vorhanden ist, sondern auch in Europa (Davis et al, 1998) sowie in der Schweiz (Wenker et al, 1998). Die zwei bekanntesten NWK-Spezies, das Lama (Lama glama) und das Alpaka (Lama pacos) sind nicht mehr vorwiegend in schweizerischen Zoos oder Zirkusunternehmen zu finden, sondern bei privaten Tierhaltern.Aufgrund der unterschiedlichen Verwendung als Zuchttiere, Woll-und Fleischproduzenten, Trekkingbegleiter oder reine Weidepfleger stehen diese Tiere zwischen Nutz-und Haustieren.…”
unclassified
“…Population, Haltung und Gesundheitsprobleme I. Hengrave Burri 1 , J. Martig 1 , H. Sager 2 , A. Liesegang 3 , M. Meylan 1 1 Wiederkäuerklinik und 2 Institut für Parasitologie der Universität Bern, 3 Institut für Tierernährung der Universität Zürich Einleitung Die Popularität der Neuweltkameliden (NWK) hat in den letzten Jahren ständig zugenommen. Ihre Population wächst stetig, nicht nur in den USA (Smith, 1998), wo das Interesse für diese Tiere schon seit Jahrzehnten vorhanden ist, sondern auch in Europa (Davis et al, 1998) sowie in der Schweiz (Wenker et al, 1998). Die zwei bekanntesten NWK-Spezies, das Lama (Lama glama) und das Alpaka (Lama pacos) sind nicht mehr vorwiegend in schweizerischen Zoos oder Zirkusunternehmen zu finden, sondern bei privaten Tierhaltern.Aufgrund der unterschiedlichen Verwendung als Zuchttiere, Woll-und Fleischproduzenten, Trekkingbegleiter oder reine Weidepfleger stehen diese Tiere zwischen Nutz-und Haustieren.…”
unclassified
“…In an epidemiological study in the United Kingdom, 4-11% of deaths amongst llamas and 17-33% of deaths in alpacas occur during the first 6 months of life. A high proportion of these deaths occur within the first week of life [31,74]. In camels, neonatal mortality can reach 50% of the calf crop in the first 10 days of life [45].…”
Section: Neonatal Emergenciesmentioning
confidence: 99%
“…Studies in the United Kingdom showed 4-11% of llama deaths were in animals under six months old (crias) with a high proportion occurring in the first week of life [1]. Enterotoxemia caused by Clostridium perfringens is a major cause of mortality in neonatal llamas [2][3][4] and type D organisms have been found in llamas in Argentina [5].…”
Section: Introductionmentioning
confidence: 99%